2005
DOI: 10.1002/pat.669
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of fluoroalkanoyl peroxides with single‐walled carbon nanotubes: application to sidewall modification of single‐walled carbon nanotubes with the introduction of fluoroalkyl groups

Abstract: Fluoroalkanoyl peroxides reacted with single‐walled carbon nanotubes (SW‐CNTs) to afford fluoroalkylated SW‐CNT derivatives under very mild conditions. Fluoroalkylated SW‐CNT derivatives [RF‐(SW‐CNT)s] thus obtained exhibited no solubility in aqueous and traditional organic media; however, RF‐(SW‐CNT)s were solubilized into water more effectively than the parent SW‐CNT by the use of fluoroalkyl end‐capped homooligomers. However, fluroalkyl end‐capped SW‐CNT cooligomers were obtained by the reactions of fluroal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…26 However, it has been shown that the electronic properties of these materials can be altered through doping 27 or functionalization. 3,[28][29][30][31][32][33][34][35][36] Recently, our group has proposed a transformation whereby one of the carbon atoms in the sidewall is replaced with a transition metal. 37,38 This newly incorporated metal atom serves as a locus for reactivity and displays characteristics of classical organometallic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, it has been shown that the electronic properties of these materials can be altered through doping 27 or functionalization. 3,[28][29][30][31][32][33][34][35][36] Recently, our group has proposed a transformation whereby one of the carbon atoms in the sidewall is replaced with a transition metal. 37,38 This newly incorporated metal atom serves as a locus for reactivity and displays characteristics of classical organometallic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The nanotube length and diameter are l and d, respectively, while σ and θ are the molecular cross-section area and coverage, respectively [71]. From Table 9, the trend between the adsorbate species and net charge transfer is clear.…”
mentioning
confidence: 95%
“…Additionally, analysis of the HOMO−LUMO gap may provide some insight. Peng and coworkers have previously suggested that charge transfer between the nanotube and adsorbate can result in a change in the conductance along the axis as described by the following relationship [71]:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Partially fluorinated polymers, especially fluoroalkyl end-capped oligomers are attractive fluorinated functional materials, because they exhibit various unique characteristic such as high solubility, surface active properties, biological activities, and nanometer size-controlled selfassembled molecular aggregates which cannot be achieved by the corresponding non-fluorinated, randomly or blocktype fluoroalkylated polymers, and low-molecular weight fluorinated surfactants [1][2][3][4][5][6][7][8][9][10][11] . The self-assembled fluorinated molecular aggregates formed by fluoroalkyl end-capped oligomers could interact with fullerene and carbon nanotube as guest molecules in aqueous media to afford fluorinated molecular aggregates-fullerene and carbon nanotube nanocomposites, respectively in aqueous solutions [12][13][14][15] . However, the shape of these fluorinated molecular aggregates is in general easily exchangeable under a variety of conditions, and the encapsulated guest molecules should have an easy releasing characteristic from the aggregates cores to their outsides under these conditions 16) .…”
Section: Introductionmentioning
confidence: 99%